Trends and Impacts of Socio-Scientific Issues (SSI) Research on Students’ Environmental Awareness: A Systematic Literature Review - Dewiyanti Fadly; Vika Puji Cahyani (CV. Science Tech Group, 2026)
Environmental problems such as climate change, pollution, biodiversity loss, and environmental degradation have increased the importance of developing students’ environmental awareness through science education. One approach widely used to address this issue is Socio-Scientific Issues (SSI)-based learning, which integrates scientific concepts with real-world social and environmental problems. This study aimed to analyze research trends, characteristics, and the impacts of SSI-based learning on students’ environmental awareness through a Systematic Literature Review (SLR). Data were collected from Scopus-indexed articles published between 2016 and 2026 using the keywords “Socio-Scientific Issues” and “students’ environmental awareness.” Bibliometric analysis was conducted using Mendeley Desktop and VOSviewer to identify publication trends, research themes, and thematic relationships. The findings indicate a significant increase in SSI-related research over the last decade, particularly in the fields of science education, environmental education, and sustainability studies. Climate change, sustainable development, environmental protection, and scientific argumentation were identified as dominant research themes. The review also shows that SSI-based learning positively influences students’ environmental awareness, critical thinking, scientific literacy, argumentation skills, and pro-environmental behavior. Furthermore, the integration of SSI with Problem-Based Learning (PBL), Education for Sustainable Development (ESD), and digital learning tools strengthens students’ engagement with environmental issues. Overall, SSI is an effective pedagogical approach for promoting environmental awareness and sustainability-oriented education. Enhancing students’ environmental awareness through SSI-based learning is a critical strategy for developing sustainability-literate citizens who are capable of addressing global environmental challenges such as climate change, biodiversity loss, and pollution, in line with Sustainable Development Goal (SDG) 4.7 on Education for Sustainable Development.